Association Between rs12037447, rs146732504, rs151078858, rs55723436, and rs6094136 Polymorphisms and Kawasaki Disease in the Population of Polish Children - Buda, Piotr; Chyb, Maciej; Smorczewska-Kiljan, Anna; Wieteska-Klimczak, Anna; Paczesna, Agata; Kowalczyk-Domagała, Monika; Okarska-Napierała, Magdalena; Sobalska-Kwapis, Marta; Grochowalski, Łukasz; Słomka, Marcin; Sitek, Aneta; Ksia̧żyk, Janusz; et al. (Frontiers in Pediatrics, 2021)
Background: Kawasaki disease (KD) is an acute self-limited febrile vasculitis that mainly affects young children. Coronary artery involvement is the most serious complication in children with KD. It is currently the leading cause of acquired cardiac disease in children from developed countries. Literature data indicate a significant role of genetic susceptibility to KD. Objective: The aim of this study was to perform the first Genome-Wide Association Study (GWAS) in a population of Polish children with KD and identify susceptible genes involved in the pathogenesis of KD. Material and Methods: The blood samples of Kawasaki disease patients (n=119) were collected between 2016 and 2020, isolated and stored at the Department of Pediatrics, Nutrition and Metabolic Diseases, Children’s Memorial Health Institute in Warsaw. The control group was based on Polish donors (n=6071) registered as the POPULOUS collection at the Biobank Lab of The Department of Molecular Biophysics in University of Lodz. DNA samples were genotyped for 558,231 Single Nucleotide Polymorphisms (SNPs) using the 24 × 1 Infinium HTS Human Core Exome microarrays according to the protocol provided by the manufacturer. In order to discover and verify genetic risk-factors for KD, association analysis was carried out using PLINK 1.9. Results: Of all 164,395 variants, 5 were shown to occur statistically (padjusted<0.05) more frequent in Kawasaki disease patients than in controls. Those are: rs12037447 in non-coding sequence (padjusted=8.329 x 10-4, OR= 8.697, 95% CI; 3.629-20.84) and rs146732504 in KIF25 (padjusted=0.007354, OR=11.42, 95% CI; 3.79-34.43), rs151078858 in PTPRJ (padjusted=0.04513, OR=8.116, 95% CI; 3.134-21.01), rs55723436 in SPECC1L (padjusted=0.04596, OR=5.596, 95% CI; 2.669-11.74), rs6094136 in RPN2 (padjusted=0.04755, OR=10.08, 95% CI; 3.385-30.01) genes. Conclusion: Polymorphisms of genes KIF25, PTRPJ, SPECC1L, RNP2 may be linked with the incidence of Kawasaki disease in Polish children.